Development of reagents for protection of equipment of water supply systems from scale and corrosion - Shuryberko, Mariia; Gomelya, Mykola; Shabliy, Tetyana; Chuprova, Kristina (Technology audit and production reserves, 2018)
The object of research is environmentally friendly water exchange systems in industry and utilities. At existing enterprises, in the process of modernizing water use systems, they often switch to the use of corrosion inhibitors for metals and scale formation. After a long period of operation of these systems, equipment replacement is not performed. One of the most problematic places of reconstruction is the presence of scale formation and corrosion products on the inner surface of heat exchange equipment. These formations reduce the efficiency of heat transfer and level the effectiveness of corrosion inhibitors and scale builders. In this paper, the effectiveness of compositions proposed as etching solutions for cleaning metal surfaces from a sedimentary deposit, as well as stabilizers of scale formation, is evaluated. In the course of the study, compositions based on inorganic acids in the presence of urotropin, urotropin with thiocarbamide were used. The research results indicate that the P-29 composition is characterized by the lowest corrosivity among the options considered. The deep corrosion rate is 0.118907 mm/year. The rate of destruction of chemically shrunk gypsum is at least 90 %. For the purpose of effective and long-term use of heat exchange equipment, it is advisable to use corrosion and scale inhibitors. The paper presents a new P-33 composition, which at a concentration of 20 mg/dm3 (water hardness 230–490 mg-eq/dm3, t=90 °C, τ=5 h) provides a stabilization effect of 56.0–93.3 %, and the anti-scale effect – 95.5–99.3 %. With an increase in the concentration of the reagent to 50 %, the stabilization and anti-scale effects reach 100 %. The developed compositions for cleaning the surfaces of heat exchange equipment based on affordable low-cost reagents, which are dominated by analogues in efficiency, are characterized by low corrosivity and ensure removal of poorly soluble chemically resistant substances (gypsum) from the metal surface. P-33 composition is superior to analogs in that it provides stabilization of the precipitated structure in gypsum solutions in the presence of calcium and magnesium carbonates at high temperatures.